Knowledge before action: Islamic learning and Sufi practice in the life of Sayyid Jalāl al-Dī n Bukhārī Makhdūm-i Jahāniyān - Steinfels, Amina M. (Studies in comparative religion, 2012)
The education of a Sufi shaykh. Initiation into the Sufi path -- Pilgrimage and travel -- Teaching and practice. Book-learning and Islamic law -- Ritual and practice -- Money, non-Muslims, women, and saints -- Served by the inhabitants of the world. A public figure -- Legacy